Implementasi Kebijakan Penataan Organisasi Sekretariat Daerah Kota Depok Provinsi Jawa Barat - Ristika Yulianti Gredenggo; Ismail Nurdin; Rizki Amalia (Journal on Education, 2023)
Administration of government in improving welfare according to the policy is expected to create good coordination in the Implementation of Structuring Policy in the Regional Secretariat Organization. This study aims to analyze how the organizational governance policies of the Regional Secretariat of Depok City, West Java Province, are implemented. The method used in this study is descriptive with a qualitative approach, where data collection techniques are carried out through interviews, observation and documentation. And the factors that influence policy implementation using Edward III's theory are the dimensions of communication, dimensions of resources, dimensions of disposition and dimensions of bureaucratic structure. The results of the research conducted show that the application of organizational structure to performance has not been followed up with equalization of positions in the preparation of SK and Tusinya. The effort that can be made by the Depok city government is to issue a mayoral regulation regarding work mechanisms or equity so that employees can work according to their scope of work.